Antioxidant Effect of Fructus Ligustri Lucidi Aqueous Extract in Ovariectomized Rats Is Mediated through Nox4-ROS-NF-κB Pathway - Wang, Lili; Ma, Rufeng; Guo, Yubo; Sun, Jing; Liu, Haixia; Zhu, Ruyuan; Liu, Chenyue; Li, Jun; Li, Lin; Chen, Beibei; Sun, Liping; Tang, Jinfa; et al. (Frontiers in Pharmacology, 2017)
Purpose: This study is designed to explore whether Fructus ligustri lucidi (FLL) exhibits antioxidant effect in ovariectomized (OVX) rats, and to identify the signaling pathway involved in this process. Methods: OVX rats were treated with FLL aqueous extract (3.5 g/kg) for 12 weeks. Serum, uteri, and tibias were harvested from the rats and the levels of total antioxidant capacity (TAC), nitric oxide (NO), malondialdehyde (MDA), 8-hydroxy-desoxyguanosine (8-OHdG), and superoxide dismutase (SOD) were determined. Changes in the levels of NF-κB-p65, phosphorylation of NF-κB-p65 (NF-κB-pp65), NF-κB inhibitor alpha (IκBα), phosphorylation of IκBα (p-IκBα), and NADPH oxidase 4 (Nox4) in uteri and tibias were determined by western blot, immunofluorescent and immunohistochemical analysis, respectively. In addition, the expression of cytochrome C (Cyto-C) and B-cell lymphoma-2 (Bcl-2) were determined in the tibias of rats. Histopathological changes in the bones were evaluated by hematoxylin-eosin staining. Bone mineral density (BMD) was determined in rat femurs by dual X-ray absorptiometry. Results: Treatment of OVX rats with FLL aqueous extract improved redox homeostasis by increasing the levels of TAC and NO as well as decreasing the levels of MDA and 8-OHdG in serum, tibias, and uteri. Further, FLL extract also downregulated the expression of Nox4, NF-κB-p65, NF-κB-pp65, and p-IκBα in the uteri and tibias. Furthermore, administration of FLL to OVX rats increased Bcl-2 expression and prevented cytoplasmic release of mitochondrial Cyto-C in the tibias. In addition, FLL treatment also improved bone microstructure and increased cortical bone thickness as well as increased BMD values in the femurs of OVX rats. Conclusions: FLL treatment may suppress oxidative stress response in OVX rats via regulating the Nox4/ROS/NF-κB signaling pathway. These results suggest the potential of using FLL as a natural antioxidant agent in preventing the development of osteoporosis.